Daniel Katz - ein Fremder in der finnischen Literatur? - Mrozewicz, Bolesław (Folia Scandinavica Posnaniensia, 2007)
The focal point of the article is the position of Daniel Katz, a writer of Jewish origin who has published in Finnish, in the Finnish literature of the second part of the 20th century. Katz has introduced new elements to Finnish writing, which until the 1960s was limited to purely Finnish problems and motifs. Literary critics and scholars have been for years engaged in a debate on whether Katz is a Finnish writer or a foreign author who writes in Finnish about problems marginal to Finns. This article attempts to answer this question.